Q: What is -2x plus 9 equals x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

2x + 1 = 9 2x = 9 - 1 2x = 8 2x/2 = 8/2 x=4

2x = -x +9

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

Related questions

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

2x+1 = 9 2x = 9-1 2x = 8 x = 4

2x + 1 = 9 2x = 9 - 1 2x = 8 2x/2 = 8/2 x=4

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1

2x = -x +9

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

(-1,-2)

(2, 1)

x=-1/2

3x = 8 x = 2.666

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3